Effect of information and information source on consumer preference for food irradiation - John A. Fox; Michael A. Boland; W. Grady (Kansas Agricultural Experiment Station Research Reports, 2003)
The effect of consumer information about food irradiation and the source of the information was studied through a survey mailed to 400 residents each of Manhattan and Topeka, Kansas. Two-thirds of the surveys contained a brochure providing answers to frequently asked questions about irradiation, one-third did not. Half of the informational brochures were altered to suggest they were from industry, half from the government. The survey questioned consumer choice between irradiated and non-irradiated ground beef patties, with price differentials from 10 cents/lb to 40 cents/lb costlier for irradiated patties. A greater price differential resulted in less preference for irradiated beef patties. The informational brochure increased the choice of irradiated patties, with that from a "government source" rather than an "industry source" being more effective (57% compared to 51%).
Keywords: Cattlemen& #x27; s Day; 2003; Kansas Agricultural Experiment Station contribution; no. 03-272-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 908; Beef; Food irradiation; Consumer preference